Characterization of a novel multi-resistant Pseudomonas juntendi strain from China with chromosomal bla VIM-2 and a megaplasmid coharboring bla IMP-1-like and bla OXA-1 - Jiang, Shiman; Li, Yaling; Bi, Kefan; Yang, Sisi; Xia, He; Li, Shengjie; Chen, Hui; Li, Lanjuan (BMC genomics, 2024)
Pseudomonas juntendi is a newly identified opportunistic pathogen, of which we have limited understanding. P. juntendi strains are often multidrug resistant, which complicates clinical management of infection. A strain of Pseudomonas juntendi (strain L4326) isolated from feces was characterized by MALDI-TOF-MS and Average Nucleotide Identity BLAST. This strain was further subject to whole-genome sequencing and Maximum Likelihood phylogenetic analysis. The strain was phenotypically characterized by antimicrobial susceptibility testing and conjugation assays. We have isolated the novel P. juntendi strain L4236, which was multidrug resistant, but retained sensitivity to amikacin. L4236 harbored a megaplasmid that encoded bla and a novel bla resistance gene variant. P. juntendi strain L4236 was phylogenetically related to P. juntendi strain SAMN30525517. A rare P. juntendi strain was isolated from human feces in southern China with a megaplasmid coharboring bla and bla . Antimicrobial selection pressures may have driven acquisition of drug-resistance gene mutations and carriage of the megaplasmid.